Транспарентність влади: польський досвід - Крет, О. (Сучасна українська політика. Політики і політологи про неї, 2011)
Досліджується польський досвід забезпечення транспарентності влади на основі реалізації соціального проекту «Прозора Польща» («Пречиста Польська»). Проаналізовано етапи реалізації проекту та його основні програми. Авторка робить висновок, що масову участь місцевих органів влади у вирішенні проблем формування транспарентної влади варто розглядати як можливість для поліпшення якості майбутньої діяльності уряду Польщі. The author investigates the Polish experience of maintenance transparency of the authorities on the basis of realization of the social project «Transparent Poland» («Prechistaja Polska»). The phases of the project and its core programs are analyzed. The conclusion is made that mass participation of local authorities in the decision of the problems of formation of transparent authorities should be considered as a possibility to improve quality of the future activity of the government of Poland.